Glucose and trehalose metabolism through the cyclic pentose phosphate pathway shapes pathogen resistance and host protection in Drosophila. - Kazek, M.; Chodáková, L.; Lehr, K.; Strych, L.; Nedbalová, P.; McMullen, E.; Bajgar, A.; Opekar, S.; imek, P.; Moos, M.; Doleal, T. (PLoS Biology, 2024)
Activation of immune cells requires the remodeling of cell metabolism in order to support immune function. We study these metabolic changes through the infection of Drosophila larvae by parasitoid wasp. The parasitoid egg is neutralized by differentiating lamellocytes, which encapsulate the egg. A melanization cascade is initiated, producing toxic molecules to destroy the egg while the capsule also protects the host from the toxic reaction. We combined transcriptomics and metabolomics, including 13C-labeled glucose and trehalose tracing, as well as genetic manipulation of sugar metabolism to study changes in metabolism, specifically in Drosophila hemocytes. We found that hemocytes increase the expression of several carbohydrate transporters and accordingly uptake more sugar during infection. These carbohydrates are metabolized by increased glycolysis, associated with lactate production, and cyclic pentose phosphate pathway (PPP), in which glucose-6-phosphate is re-oxidized to maximize NADPH yield. Oxidative PPP is required for lamellocyte differentiation and resistance, as is systemic trehalose metabolism. In addition, fully differentiated lamellocytes use a cytoplasmic form of trehalase to cleave trehalose to glucose and fuel cyclic PPP. Intracellular trehalose metabolism is not required for lamellocyte differentiation, but its down-regulation elevates levels of reactive oxygen species, associated with increased resistance and reduced fitness. Our results suggest that sugar metabolism, and specifically cyclic PPP, within immune cells is important not only to fight infection but also to protect the host from its own immune response and for ensuring fitness of the survivor.